The verbal correlations in the dictionary of Abu Hilal al-Askari are names of the remains of things in the manner of the letters of the dictionary - Aloreany, Alwah Hazam Muslah (Arab Journal for Sciences and Research Publishing, 2021)
The term verbal syndromes are often mentioned in books of Arab heritage, and mothers of literary books, It's a term that takes a place in linguistic fields, So this research aims to define this linguistic term and its characteristics, and its classifications, and its old and new status, with the explanation of four examples of application, In the dictionary of his (al-Askari) class, he called it the 'dictionary of the names of the remains of things in the style of the letters of the dictionary'The problem with research is the detection of linguistic structures containing verbal syndrome, and then their analysis and interpretation, in the (al-Askari) Dictionary of Abu Hilal, the names of the remains of things in the form of the letters of the dictionary.One of the objectives of the research is to try to provide a simple idea and a brief explanation to identify the dictionary of the remains of the (al-Askari) father of the deceased in '400 Ah', and then to analyze the verbal syndromes found in the dictionary.The study of this research therefore required a descriptive study in order to trace the verbal syndromes mentioned in the dictionary of the names of the remains of things in the style of the letters of the dictionary of Abu Hilal al-Askari, a dictionary containing many vocabulary and Arabic compositions, Accordingly, this research was entitled Semantics of Verbal Syndromes in the Dictionary of The Names of The Remains of Things by Abu Hilal al-Askari, to analyze these syndromes descriptively and with accurate scientific results.Perhaps one of the most significant linguistic findings was the following.Abu Hilal (al-Askari) Dictionary contains several verbal syndromes, with linguistic connotations.All the syndrome mentioned in the (al-Askari) dictionary is of the quality of the nominal composition.After analyzing the syndrome, it was observed that there was a semantic of verbal syndromes, one a basic lexical central indication, and the other a contextual meta-semantic.The (al-Askari) dictionary has not been without verbal syndromes.
Keywords: Names; Idiomatic Expressions; System; Abu Hilal al-Askari's Dictionary